Spinopelvic Parameters Do Not Predict the Sagittal Orientation of the Acetabulum. Issue 10 (14th October 2020) - Hatem, Munif; Nimmons, Scott J.; Khoury, Anthony Nicholas; Martin, Hal David
Background: The orientation of the acetabulum has a fundamental role in impingement and instability of the hip, and the spinopelvic parameters are thought to predict the sagittal orientation of the acetabulum (SOA). However, similar to the acetabular version (axial orientation) and inclination (coronal orientation), the cephalic or caudal orientation of the acetabulum in the sagittal plane, or SOA, may primarily be an intrinsic feature of the acetabulum itself. Purpose: To determine whether the spinopelvic parameters predict the sagittal orientation of the acetabulum in individuals without lumbar deformity. Study Design: Cross-sectional study; Level of evidence, 4. Methods: A retrospective analysis was performed in 89 patients (94 hips; 62 female, 27 male; mean ± SD age, 45.9 ± 15.4 years) without lumbosacral deformity who underwent magnetic resonance arthrogram (MRA) for assessment of hip pain. The SOA was determined in the sagittal cut MRA. A line was drawn at the distal limit of the anterior and posterior acetabular horns longitudinally to the transverse ligament, and the angle between this line and the axial plane represented the SOA. The sacral slope, pelvic incidence, and spinopelvic tilt were determined using a 3-dimensional cursor and the axial, sagittal, and coronal cuts. All MRA studies were performed with the patient in the supine position. Results: The SOA had a mean ± SD cephalic orientation of 18° ± 6.6°. No significant correlation was observed between the SOA and the sacral slope ( r = –0.03; P = .77). A weak correlation was observed between the SOA and the pelvic incidence ( r = 0.22; P = .03) and between the SOA and the spinopelvic tilt ( r = 0.41; P < .01). Conclusion: The SOA cannot be presumed based on the spinopelvic parameter. Similar to the well-known parameters to assess the axial and coronal orientation of the acetabulum, the assessment of the SOA demands acetabular-specific parameters. Additional studies are necessary to assess the SOA in asymptomatic hips, including disparities between genders. Clinically significant values for abnormal SOA of the acetabulum remain to be defined.